Advances in Theoretical and Computational Energy Optimization Processes Volume 2 - Salata, Ferdinando; Golasi, Iacopo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The paradigm in the design of all human activity that requires energy for its development must change from the past. We must change the processes of product manufacturing and functional services. This is necessary in order to mitigate the ecological footprint of man on the Earth, which cannot be considered as a resource with infinite capacities. To do this, every single process must be analyzed and modified, with the aim of decarbonising each production sector. This collection of articles has been assembled to provide ideas and new broad-spectrum contributions for these purposes.